An observational study on the challenges faced by actors in a social innovation ecosystem - Chueri, Luciana; Vasconcelos, Aline; dos Santos, Rodrigo Pereira (Proceedings of the 11th International Conference on Management of Digital EcoSystems, 2019)
A social innovation ecosystem is a set of actors from different societal sectors and their environments with legal and cultural norms, supportive infrastructures and many other elements, which enable or inhibit the development of social innovations. In this context, several issues regarding information reuse and integration can be found. In this paper, we present an observational study where a real case of an emerging social innovation ecosystem was modeled and analyzed in order to identify the challenges faced by the actors. Results show the importance of adopting digital ecosystem concepts for an approach in which social innovation actors interact and collaborate through the support provided by a common technological platform, composing what we called as Social Innovation Digital Ecosystem (SIDE). Such approach aims to support social innovation actors towards fostering collaboration, co-creation, knowledge, and information sharing and reuse, enabling the development, dissemination and generation of more effective social innovations.
Keywords: Digital; Innovation sociale; Modèle; Réservé UdeM

Redefining Education in the Digital Economy: The Role of Social Innovation-based Learning in Information Systems Education - Abhari, Kaveh; Koobchehr, Farzan; Huxford, Cyrus; Olivares, Fernando; Kohsuwan, Pocky; Sosa, Luis (Amcis 2020 Proceedings, 2020)
Social responsibility is at the core of modern Information Systems (IS) education due to increased attention by society on the ethics, human factors, and social consequences of emerging technologies. With the acknowledgement that most IS education falls short along these areas, this paper sheds light on the application of Social Learning and Social Innovation-based Learning in socially responsible IS Education. The connectivism principles were used to develop a learning model based on social innovation that was then tested by the example of an upper-division course (Systems Analysis) at a state university. The case study results suggested that the proposed learning model can help students to not only see information systems as social systems but also consider themselves as catalysts for positive change enabled by these systems. The findings also confirmed the positive impact of the proposed intervention on students' social skills. This study contributes to the future of IS education by proposing social innovation-based learning as a practical education paradigm for the digital economy.
WOS:000559924502098
Keywords: Accès gratuit sur inscription; Digital; social; Éducation; États-Unis

Commonshare: A New Approach to Social Reputation for Online Collaborative Communities - Rough, Daniel; De Paoli, Stefano; Wilson, Anna (Social Science Computer Review, 2021)
Reputation systems are a popular feature of web-based platforms for ensuring that their users abide by platform rules and regulations and are incentivized to demonstrate honest, trustworthy conduct. Accrual of "reputation" in these platforms, most prominently those in the e-commerce domain, is motivated by self-interested goals such as acquiring an advantage over competing platform users. Therefore, in community-oriented platforms, where the goals are to foster collaboration and cooperation among community members, such reputation systems are inappropriate and indeed contrary to the intended ethos of the community and actions of its members. In this article, we argue for a new form of reputation system that encourages cooperation rather than competition, derived from conceptualizing platform communities as a networked assemblage of users and their created content. In doing so, we use techniques from social network analysis to conceive a form of reputation that represents members' community involvement over a period of time rather than a sum of direct ratings from other members. We describe the design and implementation of our reputation system prototype called "commonshare" and preliminary results of its use within a Digital Social Innovation platform. Further, we discuss its potential to generate insight into other networked communities for their administrators and encourage cooperation between their users.
Place: Thousand Oaks Publisher: Sage Publications Inc WOS:000672957900001
Keywords: Digital; Réservé UdeM

Editorial : Digital social innovation: An overview and research framework - Qureshi, Israr; Pan, Shan L.; Zheng, Yingqin (Information Systems Journal, 2021)
Digital social innovation (DSI) involves the use of digital technologies in the development and implementation of innovative products, services, processes and business models that seek to improve the well-being and agency of socially disadvantaged groups or address social problems related to marginality, inequality and social exclusion (Qureshi, Pan, & Zheng, 2017; Shalini et al., 2021). Information Systems Frontiers, 22 (11), 1 - 21. https://doi.org/10.1007/s10796-020-09991-6 153 Parthiban, R., Qureshi, I., Bandyopadhyay, S., & Jaikumar, S. (2021). Social inclusion/exclusion (Diaz Andrade & Doolin, 2016; Iivari et al., 2018; Riaz & Qureshi, 2017); social inequality (Qureshi et al., 2018; Zheng & Walsham, 2008, 2021) Embedded agency of DSIrs How are DSIrs able to engage with local institutions yet bring change in these very same institutions? 151 Pandey, M., Bhati, M., Shukla, D. M., & Qureshi, I. (2021). 152 Parthiban, R., Qureshi, I., Bandyopadhyay, S., Bhatt, B., & Jaikumar, S. (2020).
Number: 5 Issu d'un numéro spécial sur la Digital Social Innovation
Keywords: Digital; Réservé UdeM

Women entrepreneurs' digital social innovation: Linking gender, entrepreneurship, social innovation and information systems - Suseno, Yuliani; Abbott, Ling (Information Systems Journal, 2021)
This article responds to increasing discourses on digital social innovation (DSI) from the perspectives of women entrepreneurs. Using the individual differences theory of gender and information technology (IDTGIT), this research explores how digital technology is used by women entrepreneurs to create opportunities in response to the challenges associated with individual identity, individual influences, social influences and structural influences. We also extend the IDTGIT by exploring how technology is used by women entrepreneurs in their DSI ventures and how technology facilitates the social impact of such ventures. This paper draws on a qualitative study using interviews with 17 women entrepreneurs in Australia, and our findings indicate that individual identity, individual influences and social and structural influences play a significant role in inhibiting women entrepreneurs' business ventures but technology helps to create opportunities for women entrepreneurs to address these factors. We also found that technology plays a role in helping women entrepreneurs to pursue social innovation in two different ways: through social innovation that is embodied by technology and social innovation that is enabled by technology. Our findings further indicate the social impact of DSI in the areas of education, employment, environment and climate, community development and progress and healthcare. The theoretical and practical implications of DSI for women entrepreneurs are provided.
Number: 5
Keywords: Australie; Digital; Réservé UdeM

Redefining Education in the Digital Economy: The Role of Social Innovation-based Learning in Information Systems Education - Abhari, Kaveh; Koobchehr, Farzan; Huxford, Cyrus; Olivares, Fernando; Kohsuwan, Pocky; Sosa, Luis (Amcis 2020 Proceedings, 2020)
Social responsibility is at the core of modern Information Systems (IS) education due to increased attention by society on the ethics, human factors, and social consequences of emerging technologies. With the acknowledgement that most IS education falls short along these areas, this paper sheds light on the application of Social Learning and Social Innovation-based Learning in socially responsible IS Education. The connectivism principles were used to develop a learning model based on social innovation that was then tested by the example of an upper-division course (Systems Analysis) at a state university. The case study results suggested that the proposed learning model can help students to not only see information systems as social systems but also consider themselves as catalysts for positive change enabled by these systems. The findings also confirmed the positive impact of the proposed intervention on students' social skills. This study contributes to the future of IS education by proposing social innovation-based learning as a practical education paradigm for the digital economy.
WOS:000559924502098
Keywords: Accès gratuit sur inscription; Digital; social; Éducation; États-Unis

Commonshare: A New Approach to Social Reputation for Online Collaborative Communities - Rough, Daniel; De Paoli, Stefano; Wilson, Anna (Social Science Computer Review)
Reputation systems are a popular feature of web-based platforms for ensuring that their users abide by platform rules and regulations and are incentivized to demonstrate honest, trustworthy conduct. Accrual of "reputation" in these platforms, most prominently those in the e-commerce domain, is motivated by self-interested goals such as acquiring an advantage over competing platform users. Therefore, in community-oriented platforms, where the goals are to foster collaboration and cooperation among community members, such reputation systems are inappropriate and indeed contrary to the intended ethos of the community and actions of its members. In this article, we argue for a new form of reputation system that encourages cooperation rather than competition, derived from conceptualizing platform communities as a networked assemblage of users and their created content. In doing so, we use techniques from social network analysis to conceive a form of reputation that represents members' community involvement over a period of time rather than a sum of direct ratings from other members. We describe the design and implementation of our reputation system prototype called "commonshare" and preliminary results of its use within a Digital Social Innovation platform. Further, we discuss its potential to generate insight into other networked communities for their administrators and encourage cooperation between their users.
Place: Thousand Oaks Publisher: Sage Publications Inc WOS:000672957900001
Keywords: Digital; Réservé UdeM

Editorial : Digital social innovation: An overview and research framework - Qureshi, Israr; Pan, Shan L.; Zheng, Yingqin (Information Systems Journal, 2021)
Digital social innovation (DSI) involves the use of digital technologies in the development and implementation of innovative products, services, processes and business models that seek to improve the well-being and agency of socially disadvantaged groups or address social problems related to marginality, inequality and social exclusion (Qureshi, Pan, & Zheng, 2017; Shalini et al., 2021). Information Systems Frontiers, 22 (11), 1 - 21. https://doi.org/10.1007/s10796-020-09991-6 153 Parthiban, R., Qureshi, I., Bandyopadhyay, S., & Jaikumar, S. (2021). Social inclusion/exclusion (Diaz Andrade & Doolin, 2016; Iivari et al., 2018; Riaz & Qureshi, 2017); social inequality (Qureshi et al., 2018; Zheng & Walsham, 2008, 2021) Embedded agency of DSIrs How are DSIrs able to engage with local institutions yet bring change in these very same institutions? 151 Pandey, M., Bhati, M., Shukla, D. M., & Qureshi, I. (2021). 152 Parthiban, R., Qureshi, I., Bandyopadhyay, S., Bhatt, B., & Jaikumar, S. (2020).
Issu d'un numéro spécial sur la Digital Social Innovation
Keywords: Digital; Réservé UdeM

Women entrepreneurs' digital social innovation: Linking gender, entrepreneurship, social innovation and information systems - Suseno, Yuliani; Abbott, Ling (Information Systems Journal, 2021)
This article responds to increasing discourses on digital social innovation (DSI) from the perspectives of women entrepreneurs. Using the individual differences theory of gender and information technology (IDTGIT), this research explores how digital technology is used by women entrepreneurs to create opportunities in response to the challenges associated with individual identity, individual influences, social influences and structural influences. We also extend the IDTGIT by exploring how technology is used by women entrepreneurs in their DSI ventures and how technology facilitates the social impact of such ventures. This paper draws on a qualitative study using interviews with 17 women entrepreneurs in Australia, and our findings indicate that individual identity, individual influences and social and structural influences play a significant role in inhibiting women entrepreneurs' business ventures but technology helps to create opportunities for women entrepreneurs to address these factors. We also found that technology plays a role in helping women entrepreneurs to pursue social innovation in two different ways: through social innovation that is embodied by technology and social innovation that is enabled by technology. Our findings further indicate the social impact of DSI in the areas of education, employment, environment and climate, community development and progress and healthcare. The theoretical and practical implications of DSI for women entrepreneurs are provided.
Keywords: Australie; Digital; Réservé UdeM